DIACHRONIC VARIATION OF LINGUISTIC TRANSPARENCY IN BRAZILIAN PORTUGUESE: THE ROLE OF THE PERCENTAGE INCREASE IN THE PRONOMINAL EXPRESSION OF SUBJECT ARGUMENT - Guerra, Alessandra Regina [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2021)
In this paper, we analyze the diachronic variation of linguistic transparency in Brazilian Portuguese. The analysis focuses on the part of the morphosyntactic system that deals with the expression of subject argument through pronoun and verbal affix, taking into account first and second person arguments. We argue that this part of the morphosyntactic system is diachronically affected by three changes in the language: percentage increase in the pronominal expression of subject argument; percentage increase in the use of voce (you) to substitute tu (you); percentage increase in the use of a gente (we) to replace nos (we). In addition, we provide data on the first of these changes, as well as a quantitative account supporting that such change contributes to decrease in transparency.
Keywords: linguistic transparency; expression of subject argument; cross-reference